2009
DOI: 10.1038/cdd.2008.194
|View full text |Cite
|
Sign up to set email alerts
|

TOM-independent complex formation of Bax and Bak in mammalian mitochondria during TNFα-induced apoptosis

Abstract: The Bcl-2 family proteins Bax and Bak are activated in response to many apoptotic stimuli. As a consequence of activation, Bax and Bak oligomerize and permeabilize the outer mitochondrial membrane to permit the release of apoptosis-inducing factors. It still remains unclear whether these proteins require components of the mitochondrial protein import machinery for their function at the mitochondria. Here, we addressed this question by using inducible RNA interference for the study of protein import in mammalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 44 publications
5
28
0
Order By: Relevance
“…Our findings are similar to those recently reported by Ross et al (42); however, in their case, Bak remained in the Bak ⌱ doublet species and only shifted when cells were induced to undergo apoptosis. To determine whether the transition we observed of Bak from the Bak ⌱ to Bak ⌱⌱ complex was the same as the transitioning observed by Ross et al (42), we induced MOMP in vitro by adding the membrane-targeted death ligand, tBid.…”
Section: Mitochondrial Outer Membrane Permeabilization Is Concomitantsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are similar to those recently reported by Ross et al (42); however, in their case, Bak remained in the Bak ⌱ doublet species and only shifted when cells were induced to undergo apoptosis. To determine whether the transition we observed of Bak from the Bak ⌱ to Bak ⌱⌱ complex was the same as the transitioning observed by Ross et al (42), we induced MOMP in vitro by adding the membrane-targeted death ligand, tBid.…”
Section: Mitochondrial Outer Membrane Permeabilization Is Concomitantsupporting
confidence: 93%
“…We observed that the size of the 400-kDa Bak complex resembled VDAC complexes previously seen by BN-PAGE (42,44,45). To determine whether VDAC2 influenced the formation of the Bak complex, we compared import and assembly of Bak in mitochondria isolated from wild type and vdac2 Ϫ/Ϫ MEFs.…”
Section: Vdac2 Is Required For Formation Of the Inactive Bak Complex-mentioning
confidence: 68%
“…(Fig. 1A), as noted by others (22,34,35). Consistent with previous reports implicating an interaction of Bak with VDAC2 (15,16,36), the large Bak complex comigrated with a complex containing VDAC (Fig.…”
Section: Baxsupporting
confidence: 87%
“…These two Bak complexes were even more clearly resolved by highresolution clear native PAGE (Fig. 1H) and were consistent with those observed during TNF-induced apoptosis of HeLa cells (34). However, when membranes were solubilized in the presence of DTT to prevent disulfide linkage or when a Bak variant lacked its N-terminal cysteine (C14S) (Fig.…”
Section: Bak Is Monomeric or In A Largesupporting
confidence: 84%
See 1 more Smart Citation